Inovasi Pasta Dough dengan Penambahan Kluwek (Pangium edule) - Gilbert Laurent; Lilis Sulandari; Niken Purwidiani; Ita Fatkhur Romadhoni (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Pasta dough, or fresh pasta, is a flour-based food product that is popular globally but has limitations in shelf life. This study aims to develop an innovative pasta dough by adding kluwek (Pangium edule), a local Indonesian ingredient, to enhance flavor, texture, aroma, and color. Kluwek was chosen due to its bioactive compounds, such as tannins, healthy fats, and minerals, as well as its potential as a natural flavor enhancer (umami) and preservative. This experimental study used variations of kluwek addition (8%, 10%, 12%) to the basic pasta dough (wheat flour, egg, salt). Data were collected through organoleptic tests by 30 panelists (trained and semi-trained) to evaluate color, aroma, taste, texture, and overall preference, as well as laboratory tests for proximate analysis (moisture, protein, fat, fiber, ash, carbohydrates, and tannins). The organoleptic test results showed that the 12% kluwek concentration produced pasta with a moderately brown color (score: 3.10), a moderate aroma (3.07), a sufficiently savory taste (3.03), and a chewy texture (3.43), which was significantly preferred over the 8% and 10% concentrations (p<0.05). Proximate analysis revealed superior nutritional content, including protein (13.80%), healthy fats (5.10%), fiber (2.05%), and tannins (0.41%). The moisture (24.05%) and ash (0.31%) levels met the SNI 3551:2015 standard for fresh pasta. In conclusion, the addition of 12% kluwek produces pasta with acceptable sensory properties and higher nutritional value. This innovation not only enriches the diversification of locally sourced pasta products but also opens opportunities for the commercialization of functional foods. Recommendations for further research include shelf-life stability testing, cyanide residue toxicity assessment, and formulation optimization with other additives.